Exercise metabolism in non-obese patients with type 2 diabetes following the acute restoration of normoglycaemia - Gaffney, Christopher J.; Mansell, Peter; Stephens, Francis B.; MacDonald, Ian A.; Tsintzas, Kostas (Hindawi Publishing Corporation, 2017)
This study investigated how acute restoration of normoglycaemia affected energy metabolism during exercise in nonobese patients with type 2 diabetes. Six subjects (mean ± SEM) aged 56.2 ± 2.7 years, with a BMI of 24.5 ± 1.5 kg/m2 and a VO2 peak of 28.7 ml/kg/min, attended the lab on two randomised occasions for a four-hour resting infusion of insulin or saline, followed by 30 minutes cycling at 50% VO2 peak. During the 4 h resting infusion, there was a greater (P < 0 0001) reduction in blood glucose in insulin treatment (INS) (from 11.2 ± 0.6 to 5.6 ± 0.1 mmol/l) than in saline treatment/control (CON) (from 11.5 ± 0.7 to 8.5 ± 0.6 mmol/l). This was associated with a lower (P < 0 05) resting metabolic rate in INS (3.87 ± 0.17) than in CON (4.39 ± 0.30 kJ/min). During subsequent exercise, blood glucose increased significantly in INS from 5.6 ± 0.1 at 0 min to 6.3 ± 0.3 mmol/l at 30 min (P < 0 01), which was accompanied by a lower blood lactate response (P < 0 05). Oxygen uptake, rates of substrate utilization, heart rate, and ratings of perceived exertion were not different between trials. Insulin-induced normoglycaemia increased blood glucose during subsequent exercise without altering overall substrate utilization.